1999
DOI: 10.1002/(sici)1097-4628(19991213)74:12<2832::aid-app7>3.3.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the solubility parameter of polyimides and the segment length of siloxane block on the morphology and properties of poly(imide siloxane)

Abstract: The dependence of morphology of the poly(imide siloxane)s (PISs) on the solubility parameter of unmodified polyimides and the molecular weight and content of ␣,-bis(3-aminopropyl) polydimethylsiloxane (APPS) has been studied. The effect of the morphology on the mechanical properties is also under investigation. The domain formation in the PISs with the APPS molecular weight M n ϭ 507 g/mol is not found until the mol ratio of APPS/PIS Ն 0.5% in the pyromellitic dianhydride/p-phenylene diamine (PMDA/p-PDA)-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…the morphology of the polymer can be altered. Jwo et al [40] reported different morphology for PI in the presence of silica and this report supported the above said statement. Thus the SEM image concluded the size, shape and morphology of the PI and its nanocomposite systems.…”
Section: Sem Analysissupporting
confidence: 85%
“…the morphology of the polymer can be altered. Jwo et al [40] reported different morphology for PI in the presence of silica and this report supported the above said statement. Thus the SEM image concluded the size, shape and morphology of the PI and its nanocomposite systems.…”
Section: Sem Analysissupporting
confidence: 85%
“…The surface morphology of the randomly segmented copolymers has been extensively studied 13, 28, 29. However, the surface morphology of the block copolymers has not been studied.…”
Section: Resultsmentioning
confidence: 99%
“…The film surface morphologies of the randomly segmented and block copolymers under POM are shown in Figure 7 except block copolymer B‐4 due to its insolubility in CHCl 3 . Since the surface free energy of polysiloxane soft block is lower than that of polyimide hard block and the difference in solubility parameters between the polysiloxane soft block and polyimide hard block is large,29–32 the polysiloxane soft block tended to segregate to the surface and many aggregates were visible under POM. Interestingly, compared with the film surface of the randomly copolymer R‐1 , the film surfaces of the block copolymers had less but bigger aggregates, which was probably because the polysiloxane soft blocks in the block copolymers were extended.…”
Section: Resultsmentioning
confidence: 99%
“…Sumitomo Bakelite Co., Ltd., prepared, as adhesive tape, polyimides modified by aminopropyl‐terminated polydimethylsiloxane (APPS) under the trade name SIM 27. All studies conducted so far that have been related to poly(imide siloxane) have focused on the content and molecular weight of the siloxane segment and properties thereby affected, such as the mechanical, electrical, and thermal properties and surface morphology, because of the incorporation of the siloxane segment and the existence of microphase separation in the poly(imide siloxane) by thermal analysis and electron microscopy 33…”
Section: Introductionmentioning
confidence: 99%